2006
DOI: 10.1200/jco.2005.04.5948
|View full text |Cite
|
Sign up to set email alerts
|

Predictive and Prognostic Value of Peripheral Blood Cytokeratin-19 mRNA-Positive Cells Detected by Real-Time Polymerase Chain Reaction in Node-Negative Breast Cancer Patients

Abstract: Detection of peripheral-blood CK-19 mRNA-positive cells is an independent predictive and prognostic factor for reduced disease-free interval and overall survival, respectively, in node-negative breast cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
149
2
14

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 258 publications
(168 citation statements)
references
References 24 publications
3
149
2
14
Order By: Relevance
“…Several studies have shown that the detection of bone marrow (DTCs) [2][3][4] or peripheral blood [CTCs; [5][6] tumor cells is associated with an increased risk of relapse and reduced survival in patients with stage I/III breast cancer. In most of the studies, the detection of CTCs was performed using CK19 as a marker of epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that the detection of bone marrow (DTCs) [2][3][4] or peripheral blood [CTCs; [5][6] tumor cells is associated with an increased risk of relapse and reduced survival in patients with stage I/III breast cancer. In most of the studies, the detection of CTCs was performed using CK19 as a marker of epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…The detection of occult tumor cells either in the bone marrow or the peripheral blood has been demonstrated to represent an independent prognostic factor for disease relapse and reduced survival [2][3][4][5][6]. Indeed, a meta-analysis involving 4,703 patients with stage I-III breast cancer confirmed the independent prognostic value of DTCs [7].…”
Section: Introductionmentioning
confidence: 98%
“…More recent reports have demonstrated the prognostic significance of CK19 mRNA-positive CTCs in patients with early stage breast cancer [103][104][105]. Studies that investigated the prognostic value of CTCs/DTCs at the time of completion of adjuvant therapy [42, 106,107] showed that the detection of DTCs [42,108] and CTCs [106] after the completion of chemotherapy is associated with an unfavorable clinical outcome [103,105]; further reviewed by Ignatiadis et al [109].…”
Section: Cytokeratin 19mentioning
confidence: 99%
“…We have reported earlier that the detection of CTCs before the initiation of adjuvant chemotherapy in patients with operable breast cancer, irrespective of the presence of axillary lymph node involvement (Stathopoulou et al, 2002;Wiedswang et al, 2003;Xenidis et al, 2006), or an oestrogen/progesterone or HER2 receptor expression (Ignatiadis et al, 2007), is also an independent factor associated with decreased DFS and OS.…”
mentioning
confidence: 94%